Two new species of the genus Symplanella Fennah (Hemiptera, Fulgoromorpha, Caliscelidae) from China - Gong, Nian; Yang, Lin; Chen, Xiang-Sheng (Zootaxa, 2020)
Two new species of the genus Symplanella Fennah, 1987 are described and illustrated from China. These are S. fulva Gong & Chen, sp. nov. and S. nigricans Gong & Chen, sp. nov. The photographs and identification keys of the new species together with other known species of the genus Symplanella are provided.